2017
DOI: 10.1016/j.chest.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulant- or Warfarin-Related Major Bleeding

Abstract: In this unselected cohort of patients with oral anticoagulant-related hemorrhage with high rates of warfarin reversal, in-hospital mortality was lower among DOAC-associated bleeding events. These findings support the safety of DOACs in routine care and present useful baseline measures for evaluations of DOAC-specific reversal agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 27 publications
3
30
0
2
Order By: Relevance
“…The accuracy of major hemorrhagic events diagnosis was the cornerstone of the SACHA study; in the majority of previous studies, no medical validation was made (33) and there were few real-life studies with medical diagnosis validation (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of major hemorrhagic events diagnosis was the cornerstone of the SACHA study; in the majority of previous studies, no medical validation was made (33) and there were few real-life studies with medical diagnosis validation (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…96 Analysis of 460 bleeds observed in patients on NOACs showed that almost 20% of those patients received vitamin K, which is useless in such clinical situations. 94 It has absolutely no possibility of any effect, but was given probably because many of these patients had a prolonged INR due to rivaroxaban. 97 Tranexamic acid, an antifibrinolytic agent effective in trauma or postpartum hemorrhages, acts as a lysine analog that impairs plasminogen activation on fibrin.…”
Section: Specific Atrial Fibrillation Patient Populations At Risk Of mentioning
confidence: 99%
“…Fresh frozen plasma is ineffective in patients bleeding on NOACs but was used in about 10% of patients reported by Xu Y et al 94 Fresh frozen plasma may be used as a plasma volume expander in patients following transfusions; however, its shortcomings are numerous, including risk of transfusion reactions, and acute heart failure.…”
Section: Specific Atrial Fibrillation Patient Populations At Risk Of mentioning
confidence: 99%
See 1 more Smart Citation
“…В исследовании RE-LY (рандомизированная оценка долгосрочной антикоагулянтной терапии) сравнивали эффекты дабигатрана с варфарином у пациентов с ФП и предшествующим инсультом или транзиторной ишемической атакой (ТИА) [26]. Были сделаны выводы, что по сравнению с варфарином, дабигатран в дозе 110 мг не уступал, а в дозе 150 мг превосходил варфарин в профилактике инсульта или системной эмболии.…”
Section: частота значительных кровотечений при применении пероральныхunclassified